2020
DOI: 10.1093/ijnp/pyz073
|View full text |Cite
|
Sign up to set email alerts
|

Polygenetic Risk Scores for Major Psychiatric Disorders Among Schizophrenia Patients, Their First-Degree Relatives, and Healthy Participants

Abstract: Background The genetic etiology of schizophrenia (SCZ) overlaps with that of other major psychiatric disorders in samples of European ancestry. The present study investigated transethnic polygenetic features shared between Japanese SCZ or their unaffected first-degree relatives and European patients with major psychiatric disorders by conducting polygenic risk score (PRS) analyses. Methods To calculate PRSs for 5 psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…As unaffected FRs share approximately half of the genetic risk of schizophrenia, PRSs for schizophrenia in unaffected FRs are intermediate between those of schizophrenia patients and HCs 29,33,34 . In addition to this evidence, we found that the PRSs for age at smoking initiation were higher in schizophrenia patients than in HCs, and those in FRs were intermediate between those in patients with schizophrenia and those in HCs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…As unaffected FRs share approximately half of the genetic risk of schizophrenia, PRSs for schizophrenia in unaffected FRs are intermediate between those of schizophrenia patients and HCs 29,33,34 . In addition to this evidence, we found that the PRSs for age at smoking initiation were higher in schizophrenia patients than in HCs, and those in FRs were intermediate between those in patients with schizophrenia and those in HCs.…”
Section: Discussionmentioning
confidence: 97%
“…The target sample ( n = 332) comprised 130 patients with schizophrenia (50 males/80 females, mean age Β± SD: 42.9 Β± 13.1 years), 56 of their unaffected FRs (40 parents/12 siblings/4 offspring, 18 males/38 females, 56.8 Β± 15.6 years), and 146 HCs (97 males/49 females, 37.2 Β± 14.1 years). All of these subjects participated in our previous study 29 . The study sample was recruited from the Schizophrenia Non-Affected Relative Project 29 , 39 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants consisted of 116 patients with SCZ (44 males/72 females, mean age Β± SD: 44.0 Β± 13.2 years), 62 unaffected FRs (29 mothers/19 fathers/8 sisters/2 brothers/3 offspring, 24 males/38 females, 59.4 Β± 14.5 years), and 146 HCs (96 males/50 females, 37.0 Β± 15.2 years). The study sample was recruited from the Schizophrenia Non-Affected Relative Project at Kanazawa Medical University ( Ohi et al, 2019b, 2020 ). All participants were of Japanese descent.…”
Section: Methodsmentioning
confidence: 99%